Kasus Toksoplasmosis Serebri Tak Terduga dengan Gambaran Radiologi yang Menyerupai Keganasan - Cempaka Harsa Sekarputri; Anisia Indiralia; Roebijanti (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2022)
ABSTRACTToxoplasmosis was Toxoplasma Gondii infection. In HIV-infected patients, the prevalence of toxoplasma infectionranges was 3-97%. Diagnosis cerebral toxoplasmosis almost failed to recognized varians clinical and radiologicalfeatures on organism identifiied from brain biopsy which difficult to extract from alive patient. This case reportdiscussed cerebral toxoplasmosis of brain biopsy HIV positive patient which unknown status HIV patient, previously.A 52-year-old male patient came complained not only loss of apatit and dizzy two months ago, but also fainted.MSCT Scan with and without contrast showed right temporooccipital glioblastoma. Brain MRI showed a lesion on theright temporoparietal area with perifocal edema pressing on the right lateral ventricle. Microscopical feature showedglial tissue containing large areas of necrosis with karyorrhexis debris, PMN and mononuclear leucocyte infiltration,scaterred of tachyzoites and bradyzoites, no signs of malignancy. HIV serological examination was confirmed and thepatient's results were found to be anti-HIV reactive. Conclusion diagnosis as cerebral toxoplasmosis.